IMPLEMENTASI BAURAN PEMASARAN TERHADAP UMKM KULINER DI WILAYAH KELURAHAN MERUYA SELATAN - Alvita Sari (Jurnal Pengabdian Masyarakat Nasional, 2022)
ABSTRACTThis community service program is motivated by the many Culinary MSMEs in the South Meruya sub-district area which have difficulties in the marketing aspect. Based on the conditions above, efforts need to be made to help culinary MSMEs get up and improve their business activities so that their productivity and turnover will gradually increase again. For this reason, the Community Service Team from the Faculty of Economics and Business, Mercubuana University, Jakarta, consisting of lecturers and students, helps culinary MSMEs, especially in the South Meruya Village, Kembangan District, West Jakarta with the "Competitiveness System Workshop" program. comprehensive program to provide encouragement to the community and Culinary MSMEs.The aim of this program is to be able to create 'Job creation', so that micro entrepreneurs can be accommodated, and given workshops. Later Culinary MSME actors who have met the criteria for upgrading can continue to develop. On the other hand, this new normal is actually expected to be a momentum for good opportunities for local business actors to rise and move forward. The objectives of this Community Service are: (1) To develop and enhance an entrepreneurial spirit, high trust and independence. (2) To increase marketing knowledge of the basic needs of culinary MSMEs (3) To help culinary MSMEs understand the marketing mix which consists of 4 P (Product, Price, Place, Promotion). In order to increase competitiveness in living its business life. Keywords: Competitiveness system workshop, 4 P, New Normal